Now's your time my lads - Whigs & Tories. Christians Jews & Turks - no distinction made - Heath, William, 1795-1840 - also known as Paul Pry ? (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
Recruiting Party
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-1837; Wellington, Arthur Wellesley, Duke of, 1769-1852